Pengaruh Social Media Marketing Terhadap Pertumbuhan Bisnis Online - Nuraeni HR, Leni; Putri, Liska Zahara; Octavianus, Billy; Sanggya HB, Ahimsa; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Social media marketing (SMM) has become one of the main tools for online businesses to increase growth. This research aims to identify the influence of marketing strategies via social media on the growth of online businesses in Indonesia. Using quantitative methods through a survey of 200 online business owners, this research found that the variables of customer engagement, increasing brand visibility, and cost efficiency have a significant influence on online business growth. This study shows the importance of optimizing SMM strategies to increase competitiveness in the digital era.